Application of CdTe (CdZnTe) detectors for radioactive waste characterization - Dovbnya, N.A.; Karasyov, S.P.; Kutny, V.E.; Rybka, A.V.; Shlyakhov, I.N.; Uvarov, V.L. (Вопросы атомной науки и техники, 2002)
The radiation detectors based on wide-zone semiconductor CdTe (CdZnTe) monocrystals have promising advantages for their application in investigation (characterization) of radioactive waste. Among these advantages there are the wide range of photons flux and energy, high registration efficiency and satisfactory energy resolution without deep cooling of the detector. This report discusses the obtained data concerning radiation stability of detectors, influence of different conditions (filters, collimators, registration channel fill etc.) on their energy resolution in spectrometric regime, as well as a dependence of radionuclide identification accuracy on detector size.